Primera experiencia colombiana en construcción de pilas de agregado compacto - geopier impact - en un proyecto de vivienda de interés social (2013)
Soil improvement techniques provide alternative solutions in function of the type of soil and the size of the structure, in order to enable any terrain, to provide a secure foundation, in terms of capacity bearing and deformability in the long term (settlements), any work of engineering. In the face of complex situations, imposed by the characteristics of the deposit, opt by a conventional deep foundation (piles pre-excavated or driven and a plate-pile system) does not always efficiently solve a mode of foundation, more for reasons of economic nature than by the available technique, by the magnitude of the expected settlements and the conditions imposed by The deposit. In our environment, the procedures to improve the foundation soils of mass are not very common, as a consequence of the lack of knowledge of existing technologies and also the impossibility of accessing them due to to the low offer that is offered.